[Re] reading perspecta : the first fifty years of the Yale Architectural journal (The MIT Press, 2004)
"The material included here is organized chronologically by issue. Each issue opens with a statement by one of the editors discussing the historical context and the reasoning behind the selections made. Robert A.M. Stern writes introductions for issues 1 through 9/10, Alan Plattus, 11 through 20, and Peggy Deamer, 21 through 30. Each issue also includes the original editor's introduction, if one was written"--σ. xiii.